M, king's bodyguard : a novel - Leonard, Niall (Pantheon Books, 2021)
"Gathering intel, chasing leads, and cracking heads are all part of a day's work for Detective Chief Superintendent William Melville, bodyguard to Queen Victoria's son and heir to the throne, Prince Albert. But when the Queen dies, prompting most of Europe's royalty to converge on London for the funeral, Melville receives a tip about a planned attempt on the German Kaiser's life led by a mysterious anarchist known as Akushku. As Melville and his German counterpart, Gustav Steinhauer, race to uncover exactly what Akushku has planned, they find themselves drawn into a world of brutal violence, illicit romance, and bitter class warfare. And all the while, Akushku dances just out of reach, ensnaring rich and poor alike in his web. As the day of the funeral approaches, Melville realizes that far more than the Kaiser's life is at stake--if he can't reach Akushku in time, he risks the destruction of the very realm he's sworn to protect"--